2010
DOI: 10.1021/ic100963r
|View full text |Cite
|
Sign up to set email alerts
|

Monomeric Square-Planar Cobalt(II) Acetylacetonate: Mystery or Mistake?

Abstract: No evidence was found for the existence of a previously reported mononuclear square-planar form of unsolvated cobalt(II) acetylacetonate, Co(acac)(2), in all samples that have been obtained by using a variety of preparative techniques and crystallization conditions. It was confirmed that the structure of tetramer Co(4)(acac)(8), reported back in 1964 by Cotton and Elder, is correct, the synthesis is reproducible, and the bulk material corresponds to single-crystal data. Additionally, the title compound can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 49 publications
2
24
0
Order By: Relevance
“…There is a large family of tetranuclear Co II complexes, and most of these clusters have Co 4 O 4 cubane or defective dicubane cores (Habib et al, 2012;Gao et al, 2015;Scheurer et al, 2015;Ahmed et al, 2007;Zhang et al, 2011Zhang et al, , 2014. Only a few complexes possesses a linear tetranuclear Co II core (Barrios et al, 2009;Aguilà et al, 2011;Irving et al, 1975;Vreshch et al, 2010).…”
Section: Figurementioning
confidence: 99%
“…There is a large family of tetranuclear Co II complexes, and most of these clusters have Co 4 O 4 cubane or defective dicubane cores (Habib et al, 2012;Gao et al, 2015;Scheurer et al, 2015;Ahmed et al, 2007;Zhang et al, 2011Zhang et al, , 2014. Only a few complexes possesses a linear tetranuclear Co II core (Barrios et al, 2009;Aguilà et al, 2011;Irving et al, 1975;Vreshch et al, 2010).…”
Section: Figurementioning
confidence: 99%
“…The user can copy the resulting image to the clipboard in vector form and use it for article preparation (Vreshch et al, 2010); an example is shown in Fig. 2.…”
Section: Functions and Featuresmentioning
confidence: 99%
“…This has been observed in a variety of different systems (Yun et al, 1999;Lindoy et al, 1977;Rogachev et al, 2007;Castro et al, 1992). Within this class of compound, there is a special group where the M(acac) n units are coordinated to naked cations, producing heteropolymetallic complexes with different nuclearity and dimensionality (Shibata et al, 1984;Atencio et al, 2004;Greaney et al, 1975;Troyanov et al, 1999;Vreshch et al, 2010).…”
mentioning
confidence: 93%